The Role of the National Service Scheme in Fostering Social Skills Among Engineering Graduates - Lobo, Sonia; Nekkar, Srinivas; B., Ramakrishna; Chiplunkar, Niranjan N. (Journal of Engineering Education Transformations, 2025)
This study embarks on a captivating journey into the realm of National Service Scheme (NSS) engagement, delving deep into its impact on the multifaceted landscape of social skills development among engineering graduates. With data meticulously collected from engineering graduates, who graduated from NMAM Institute of Technology between the years 2021 and 2023, we employ rigorous statistical analysis, guided by SmartPLS 4.0, to unveil the intricate connections between NSS engagement outcomes, vital mediating variables, and the ultimate manifestation of these synergies in the form of overall social development. Through a panorama of hypotheses testing, mediation analysis, and meticulous exploration, our findings offer compelling insights into the transformative potential of NSS engagement. These revelations extend a resonating call to educators, employers, and policymakers to collaboratively nurture an empowered generation poised to flourish within a socially interconnected world.